The complete mitochondrial genome of Cheilinus oxycephalus (Perciformes: Labridae) - Liang Guo; Nan Zhang; Ke-Cheng Zhu; Hua-Yang Guo; Bao-Suo Liu; Dian-Chang Zhang (Mitochondrial DNA. Part B. Resources, 2019)
Cheilinus oxycephalus is a marine fish species, belonging to the family Labridae and naturally distributed in Indo-Pacific waters. We obtained the first complete mitochondrial genome of this species using next-generation sequencing technology. This genome is 17,698 bp, and contains 13 protein-coding genes, 2 rRNAs, 22 tRNAs, and a D-loop region. These genes are mostly encoded on the heavy strand except for ND6 and eight tRNA genes. The AT content is 52.32%. These characteristics are similar to other bony fish. This mitochondrial genome would be used as a resource for phylogenetic reconstruction.